Investigation of Diffuse Lamb Wave Sensitivity to the Through-Thickness Notch in Structural Health Monitoring of Composite Objects - Samaitis, V.; Mazeika, L. (Elektronika ir Elektrotechnika, 2014)
Modern engineering constructions are made from various kinds of multi-layered composites. Due to safety and economic reasons such objects should be monitored in order to detect the originating defects. Ultrasonic guided waves are very powerful inspection technique, due to ability to propagate long distances and sensitivity to the non-homogeneities. However due to multimodal, dispersive and environmental sensitive character the detection of defects using guided waves is complicated and requires advanced signal processing techniques. In this paper two signal processing techniques for detection of the originating defects with diffused Lamb waves was proposed and experimentally verified detecting the through thickness notch type defects in GRFP plate. DOI: http://dx.doi.org/10.5755/j01.eee.20.3.6690